Running work capacity over critical power: a variable rather than a constant parameter - Ruiz-Alias, S. A.; Ñancupil-Andrade, A. A.; Pérez-Castilla, A.; Garcia-Pinillos, F. (Sports Engineering, 2024)
The work capacity over critical power is theoretically defined by the curvature constant. However, this parameter has been characterized by a large standard error of the estimate. Therefore, this study aims to determine the validity of this parameter to represent the work performed over critical power on different time trials along the severe intensity domain. Athletes performed four-time trials (3, 5, 10 and 20 min) in a two-week training period on a 400-meter outdoor track. The mean power output of each time trial was measured through the Stryd power meter, and the inverse of the time model was used. The work depletion was modelled in each time trial until exhaustion. The standard error of the estimate was 2.4 (1.0) % for critical power and 12.3 (4.3) % for work over it. Although no significant differences were reported between the work estimated by the critical power model and the one performed on each time trial (P = 0.058), the 95% confidence intervals revealed potential significant discrepancies at the 10-min (-1.4 [-3.1 to 0.3] kJ) and 20-min (2.2 [-0.1 to 4.6] kJ) time trials, respectively. If the work estimated by the critical power model were used, subjects would have reached exhaustion at -8.0 [-19.4 to 3.3] % for the 10-min time trial, and at 13.3 [-2.8 to 29.5] % for the 20-min time trial. Thus, athletes and practitioners are encouraged to consider the specific work of the duration of interest at the severe intensity domain when monitoring with power in running.